Collaborative process improvement to enhance injury prevention in child death review. (27th January 2011) - Johnston, Brian D; Bennett, Elizabeth; Pilkey, Diane; Wirtz, Stephen J; Quan, Linda
Abstract : Objective: To increase the number and quality of injury prevention recommendations made by Washington State (USA) child death review teams. Design: Before and after study design involving four intervention teams and 21 comparison teams. Methods: Intervention teams received injury prevention training, collaborative process improvement coaching, and access to web based prevention resources. An equal number of randomly selected child death review case reports filed with the state before the intervention by the intervention and comparison teams were included in the baseline sample. All reports submitted by the intervention and comparison teams after the intervention were included in the follow-up sample. Reports were scored on the completeness of prevention related data elements and on the quality of written prevention recommendations. Results: Data completion for prevention relevant items increased in intervention teams from 73% at baseline to 88% at follow-up. In comparison teams, this measure fell from 77% to 56% over the same period. The quality of written recommendations produced by intervention teams increased from 4.3 (95% CI 3.4 to 5.1) to 7.6 (95% CI 6.7 to 8.5), while comparison teams showed no significant change (4.0 (95% CI 2.5 to 5.3) to 3.7 (95% CI 2.2 to 5.2)). Specifically, improvements were noted in the identification of evidence based best practices and the development of clear, actionable written recommendations. Conclusion: Injury prevention recommendations are generated in the systematic local review of child deaths. This process can be analysed, measured, supported, and improved.